A fuzzy assessment framework to select among transportation investment projects in Turkey - Ozkir, Vildan; Demirel, Tufan (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Selecting the best transportation investment project (TIP) is often a difficult task, since many social, environmental and economic criteria have to be considered simultaneously. Evaluating a set of different projects, especially the best set of alternatives, portfolios, is even more complex. Pursuing the goal of selecting the best TIP portfolio, we propose a fuzzy assessment method to aid the selection process of a multi-criterion project by utilizing the concept of entropy and interval normalization procedure in a fuzzy analytic hierarchy process (F-AHP). Then, regarding this informative phase, we propose a fuzzy linear programming model to select the best TIP portfolio under uncertain cost pressure. A real case study is conducted to illustrate the efficiency of the proposed method. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Entropy; Fuzzy AHP; Fuzzy linear programming; Project portfolio selection; Transportation; DECISION-MAKING; NUMBERS; AHP; Computer Science; Engineering; Operations Research & Management Science